2021
DOI: 10.1088/1748-0221/16/01/p01024
|View full text |Cite
|
Sign up to set email alerts
|

Initial trials of a dose monitoring detector for boron neutron capture therapy

Abstract: In this study, we present results of initial trials of a scintillator-over-fiber detector system with a silicon photomultiplier readout designed at Budker Institute of Nuclear Physics. The results demonstrate that the proposed system, using a pair of boron-enriched and boron-free scintillators, could be successfully used for monitoring of thermal neutron flux and estimation of irradiation dose. Nevertheless, it is necessary to optimize the design of the detector head components to ensure long time detector sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…We concluded that, before irradiating the mice, beam verification, with its component spatial distribution and volumetric dose-distribution analysis, is important. Therefore, in a recent study, spatial distribution of the beam components from this accelerator was experimentally analyzed by using a water phantom to provide actual beam-component distribution in comparison to the calculated parameters [ 49 ]. Those results will be used for dose calculation in further radiobiological experiments at the Budker Institute of Nuclear Physics accelerator, and these methods can be applied to other accelerator-based neutron sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We concluded that, before irradiating the mice, beam verification, with its component spatial distribution and volumetric dose-distribution analysis, is important. Therefore, in a recent study, spatial distribution of the beam components from this accelerator was experimentally analyzed by using a water phantom to provide actual beam-component distribution in comparison to the calculated parameters [ 49 ]. Those results will be used for dose calculation in further radiobiological experiments at the Budker Institute of Nuclear Physics accelerator, and these methods can be applied to other accelerator-based neutron sources.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the neutron beam and its contamination by fast neutrons and photons have been described previously [ 47 , 48 ]. Spatial distribution of the beam components was studied parallel to the current research, using a water phantom explicitly set up to provide experimental rather than computational data [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Of course, the proposed method can be used to measure the boron dose, but it turned out that it is easier and more reliable to measure it using our developed small-sized neutron detector with a polystyrene cast scintillator with boron (19). The results of measuring the spatial distribution of the boron dose have been reported elsewhere (20,21) Thus, all four components of the equivalent dose can be measured: the c-ray dose, with gamma-ray dosimeters; the boron dose, using a neutron detector with a polystyrene cast scintillator with boron; and the sum of the fast neutron dose and nitrogen dose, using the method described above.…”
Section: Mixed Irradiationmentioning
confidence: 96%
“…A small-sized neutron detector (1 mm × 1 mm in diameter) with two cast polystyrene scintillators, one of which is enriched in boron, has been developed and is being used for dosimetry of boron dose and γ-ray dose [33]. Figure 5 shows the result of measurements of the depth distribution of boron dose and γ-ray dose in a water phantom 33 × 33 × 31.5 cm 3 close to the lithium target at 2.05 MeV 1 mA proton beam.…”
Section: Dosimetrymentioning
confidence: 99%